Effectiveness of dye sensitised solar cell under low light condition using wide band dye - Sahmer, A.Z. (American Institute of Physics Inc., 2015)
Dye sensistised solar cell (DSC) based on nanocrystalline TiO 2 has the potential to be used in indoor consumer power application. In realizing this, the DSC must be optimized to generate power under low lighting condition and under wider visible light range. The use of wide band dye N749 which has a wider spectrum sensitivity increases the photon conversion to electron between the visible light spectrums of 390nm to 700nm. This paper reports the study on the effectiveness of the dye solar cell with N749 dye under low light condition in generating usable power which can be used for indoor consumer application. The DSC was fabricated using fluorine doped tin oxide (FTO) glass with screen printing method and the deposited TiO 2 film was sintered at 500Â°C. The TiO 2 coated FTO glass was then soaked in the N749 dye, assembled into test cell, and tested under the standard test condition at irradiance of 1000 W/m 2 with AM1.5 solar soaker. The use of the 43T mesh for the dual pass screen printing TiO 2 paste gives a uniform TiO 2 film layer of 16 Î¼m. The low light condition was simulated using 1/3 filtered irradiance with the solar soaker. The fabricated DSC test cell with the N749 dye was found to have a higher efficiency of 6.491 under low light condition compared to the N719 dye. Under the standard test condition at 1 sun the N749 test cell efficiency is 4.55. The increases in efficiency is attributed to the wider spectral capture of photon of the DSC with N749 dye. Furthermore, the use of N749 dye is more effective under low light condition as the V OC decrement is less significant compared to the latter. Â© 2015 AIP Publishing LLC.